Effects of plastic particles on germination and growth of soybean (Glycine max): A pot experiment under field condition. (1st March 2021) - Li, Bintao; Huang, Shan; Wang, Haoming; Liu, Mengjuan; Xue, Sha; Tang, Darrell; Cheng, Wanli; Fan, Tinglu; Yang, Xiaomei
Abstract: Plastic residues have become a serious environmental problem in areas where agricultural plastic film are used intensively. Although numerous of studies have been done to assess its impacts on soil quality and crop yields, the understanding of meso-plastic particles effects on plant is still limited. In this study, low density polyethylene (PE) and biodegradable plastic (Bio) mulch film were selected to study the effects of meso-plastic debris on soybean germination and plant growth with the accumulation levels of 0%, 0.1%, 0.5% and 1% in soil (w: w, size ranging 0.5–2 cm) by a pot experiment under field condition. Results showed that the germination viability of soybean seeds was reduced to 82.39%, 39.44% and 26.06% in the treatments with 0.1%, 0.5% and 1% added plastic debris compared to the control (CK), respectively, suggesting that plastic residues in soil inhibit the viability of soybean seed germination. The plastic debris had a significant negative effect on plant height and culm diameter during the entire growth stage of soybean. Similarly, the leaf area at harvest was reduced by 1.97%, 6.86% and 11.53% compared to the CK in the treatments with 0.1%, 0.5% and 1% plastic debris addition, respectively. In addition, the total plant biomass under plastic addition was reduced in both the flowering and harvesting stages, compared to the CK. For the different type of plastic residues, plant height, leaf area and root/shoot ratio at group PE were significantly lower than those of groups treated by Bio. In conclusion, PE debris had a greater negative effects on plant height, culm diameter, leaf area and root/shoot ratio while Bio debris mainly showed the adverse effects on germination viability and root biomass especially at the flowering stage. Therefore, further research is required to elaborate plastic particles' effects on different stages of crops and soil quality. Graphical abstract: Image 1 Highlights: Seed germination and soybean growth were investigated by pot experiment with plastic addition. The significant negative effects of plastic on germination viability were observed but not rate. Plastic types and levels showed different effects on plant growth. Bio plastic affected plant growth strongly at the flowing stage while PE at the harvesting stage. Abstract : Low density polyethylene negatively affected plant height and culm diameter while biodegradable plastic significantly inhibited germination viability and root biomass at the early stage of soybean growth.